ChemInform Abstract: Urea/Thiourea as Ammonia Surrogate: A Catalyst‐Free Synthesis of 2‐Substituted 2, 3‐Dihydroquinazolin‐4(1H)‐ones/Quinazoline‐4(3H)‐ones. Issue 43 (21st October 2014) - Naidu, P. Paradesi; Raghunadh, Akula; Rao, K. Raghavendra; Mekala, Ramamohan; Babu, J. Moses; Rao, B. R.; Siddaiah, V.; Pal, Manojit
Abstract The procedure is operationally simple and does not involve the use of any metal, other toxic, expensive catalysts or reagents and inert atmosphere.